Symposium Celebrating Women Surgeons Around the World - Roman, Sanziana; Jimenez, Maria; Odubu, Fualal; Chereau, Nathalie; Henne-Bruns, Doris; Yip, Cheng Har; Howle, Julie; Patti, Marco Giuseppe (Springer Verlag (Germany), 2018)
Introduction